Concepções de alunos concluintes do curso de Pedagogia sobre a docência: interfaces com a identidade profissional - Delgado, Adriana Patricio (2015)
The present work aims to study the views about the teacher profession expressed by senior students of the Pedagogy Major from a private Higher Education Institution, located in the city of São Paulo. We aimed to design a profile of those senior students of the Pedagogy major from the mentioned institution, as well as investigate which identity(ies) those students, throughout the stage of initial formation, build and which conception(s) they attribute to the teacher profession. In order to develop the investigation, we used methodological procedures of qualitative research (by means of interviews and dialogued exercise of analysis, with varied groups of students, documents and situations of the profession); and of quantitative research (by means of questionnaires), having as subjects 90 senior students of the Pedagogy major that answered the questionnaire and 10 of those who were interviewed. Besides the field research, we also used, as an investigative resource, the analysis of legal and institutional documents of the formative structure of the Pedagogy major. This study was guided by the main hypothesis that the students enroll in the major with a romanticized and naturalized conception of the teacher profession, that has come from the process of primary and secondary socialization, and that conception would be kept almost unaltered during the initial formation, reflecting on fragile and non-critical practices and expressions, permeated by common sense knowledge and by acquired technical-scientific knowledge. Authors such as Berger and Luckmann (socialization process), Claude Dubar (professional identity), Maurice Tardif (teacher knowledges), Pérez Gómez (school culture and teacher culture) and Carlos Marcelo Garcia (teacher professional development) contribute to the theoretical support for the research development. The results confirm the investigated hypothesis